IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA - Rega Dian Kusuma; Emi Pujiastuti; Mulyono (Jurnal Ilmiah Tarbiyah Umat, 2024)
This research aims to describe whether learning using the project based learning (PjBL) model is effective in improving students' mathematical literacy skills at Bina Nusantara Vocational School, Mranggen, Demak. This research was conducted as a quasi-experiment, namely testing only one class group before and after the test. The research population was all classes XI TKJJ 1 as the experimental class and XI TKJJ 2 as the control class. The aim of this research is to improve students' mathematical abilities which are assessed using the essay style examination method. The use of inferential statistical analysis techniques is used to analyze test result data using project-based learning (PjBL) as a means of improving students' mathematical abilities. Inferential statistics were used to test the research hypothesis using the paired sample t test with a significance level of 0.05. The research results show that students' skills taught using the PjBL model are better. This is shown by the significance results of the T test of 0.000<0.05, which means that the PjBL learning model has an influence and improvement on students' mathematical literacy at SMK Bina Nusantara Mranggen. The N-Gain score has an average of 69.38 or 69.38%. then this percentage is an effective stage in implementing the project based learning (PjBL) learning model